Remote Sensing of Algal Blooms in Lake Mývatn, Iceland - Johanne Cornelia van Linge 1994- (2019)
Lake Mývatn in Iceland is a eutrophic lake well-known for its unique ecosystem. Planktonic cyanobacteria are of vital importance to its ecosystem. Cyanobacterial blooms in the water column shade the bottom and reduce growth of benthic macrophytes; its increased frequency and duration have resulted in major reduction in benthic green algae, including the near disappearance of the rare Marimo balls. For the past 50 years the ecosystem has been monitored in considerable detail, however no research using remote sensing on algae or cyanobacteria has been done for Lake Mývatn. Previous research for other turbid inland waters provides various methods of quantifying algal and cyanobacterial blooms by estimating concentrations of their indicators; chlorophyll-a (CHL) and phycocyanin (PC). This study tested two CHL and one PC quantification methods on Lake Mývatn for the summers of 2016 and 2018 using multispectral satellite images from Landsat 8, Sentinel-2 and Advanced Land Imager. CHL and PC concentration maps were computed and validated with in-situ concentration measurements. The overall accuracy of the three methods were R2=0.09 (CHL1), R2=0.11 (CHL2), and R2=0.07 (PC). The results show that applying these methods in a new study area is nontrivial. In order to accurately predict algae pigment concentrations, method optimisation should be performed with in-situ spectral data. Once the newly proposed method shows statistically significant results, concentration maps can be created of Lake Mývatn for future and past satellite images. This can provide insight into algal and cyanobacterial blooming in Lake Mývatn and its influence on the lake’s ecosystem. Mývatn er þekkt fyrir einstakt vistkerfi, og gegna blágrænar bakteríur þar mikilvægu hlutverki. Mikill bakteríublómi við yfirborð getur þó skyggt á lífverur við botninn, og aukin tíðni og lengd slíkra blóma hefur valdið skaða á grænþörungum þar, þ.á m. svokölluðum kúluskít, sem er nokkuð fágætur. Lífríki Mývatns hefur verið vaktað fremur ítarlega undanfarin 50 ár, en ...